Giulia Una donna nella Toscana dei Medici - Manno Tolu, Rosalia (Fonti storiche e letterarie - Edizioni cartacee e digitali, 2020)
Giulia is a maiden abandoned at the birth in Florence of Francesco I dei Medici and Bianca Cappello, who has already been the subject of historical research and some re-elaboration in literary and cinematographic terms. Thanks to the richness of the sources now found, a completely new and exhaustive biography of this 16th century woman is presented, with an unpublished version of her personality and history. Florence, the Casentino and the Valdinievole are the places of her life, which fully reflects the condition of women in her era, faced by Giulia with courage and determination. The discourse develops on two intertwined planes, that of historical analysis and that of its narrative integration, with the hypothetical reconstruction of the areas left in the shadows. This book enters by right into historiographical traditions now widely codified and into a literary tradition defined by Giacomo Debenedetti as 'historiography of interiority'.